Measurement of the Body Physical Parameters by Bioelectrical Impedance Method in Individuals Survived after Covid-19 - Sert, Cemil; Gökçe, Yasin; Kurtuluş, Şerif (European Journal of Therapeutics, 2023)
Objective: The coronavirus disease 2019 (Covid-19) has significantly affected human health around the world, causing many complications. However, it is not fully understood how the body compositions of individuals affected in the short or long term after disease. In this study, we aimed to show the effects of Covid-19 on body composition and phase angle values, using Bioelectrical Impedance Analayser. Methods: Subjects were selected from individuals in the 18-60 age group, who had survived COVID-19 disease. 33 individuals who had survived it 1-3 months ago, and 30 individuals who had survived it 3-6 months ago were included in the study. Results: Effects of COVID-19 on basal metabolism and body composition and the ratio of damaged cells in the body after the disease were determined. Basal metabolic rate, lean body mass, body cell mass, total body fluid, intracellular fluid, and phase angle values were found to be significantly changed in the 3-6 months range compared to that of 1-3 months. Conclusion: These results indicate that the basal metabolism and body composition parameters of the body become better, and the proportion of damaged cells decreases as time goes on after suffering COVID-19, reaching values close to normal in 1-3 months and quite better values in 3-6 months. It can be concluded that, although covid-19 influences body composition parameters and cell integrity in survivors of Covid 19 disease, these effects are limited to 3-6 months.